2015
DOI: 10.1111/jog.12803
|View full text |Cite
|
Sign up to set email alerts
|

Infertility work‐up: To what degree does laparoscopy change the management strategy based on hysterosalpingography findings?

Abstract: Patients with both unilateral tubal occlusion and bilateral tubal occlusion on HSG should be reevaluated with LS to determine the appropriate management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(47 reference statements)
3
5
1
1
Order By: Relevance
“…We found 93% accuracy of HSG in tubal pathology diagnosis, similar results were reported by previous studies [16,17]. Lavy, et al [18] concluded that in 95% of patients with normal HSG or suspicious unilateral obstructed tube, laparoscopy is not indicated, and patient management will not be altered.…”
Section: Methodssupporting
confidence: 89%
“…We found 93% accuracy of HSG in tubal pathology diagnosis, similar results were reported by previous studies [16,17]. Lavy, et al [18] concluded that in 95% of patients with normal HSG or suspicious unilateral obstructed tube, laparoscopy is not indicated, and patient management will not be altered.…”
Section: Methodssupporting
confidence: 89%
“…Based on our study and results of previous literature [6,20,21,30,31], we can conclude that HSG is a valuable imaging modality for evaluating the genital tract of an infertile female; invasive procedures like laparoscopy and hysteroscopy are not indicated in patients with normal HSG findings and patients may be managed conservatively. Patients who had a pelvic disease or showing tubal obstruction on HSG needs further evaluation by laparoscopy.…”
Section: Discussionsupporting
confidence: 59%
“…The reported accuracy differed between studies concerning tubal obstruction (level and side of obstruction) [19][20][21][22]. It was more accurate in distal than proximal Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Özellikle olumsuz sonuçlarda HSG'nin geçerliliği yüksektir. IVF ile doğrudan devam etmek yerine L/S yapmak hamilelik süresini geciktirebilse de, HSG'de bilateral tubal oklüzyonlu hastaların önemli bir kısmı L/S sonrası yönetim planı değişikliği nedeniyle IUI'ye yönlendirilebilir (11). Aynı şekilde diğer bir çalışmada da HSG bulguları, özellikle bilateral proksimal tubal oklüzyon için pozitif prediktif değer göstermekle birlikte, HSG'nin tubal açıklığı doğru bir şekilde tanımlamak için sınırlı bir değeri olduğu görülmüştür.…”
Section: Bulgularunclassified